Model for Development of a Business Strategy for Renewable Energy Technology Services - Sembiring, Noor; Krisna, Nandan Lima (International Journal of Energy Economics and Policy, 2019)
The purpose of this study is to formulate a model of the current business position of technology services in the field of renewable energy. The method used in this study is a research method with a qualitative approach, through descriptive analysis. To find information on internal resources for technology business services in the field of renewable energy and obtain organizational response to external environmental conditions, focus group discussions were held with key people in the field of renewable energy at The Agency for the Assessment and Application of Technology (BPPT). Based on the results of the analysis, it was found that the development of the business strategy already being carried out was by (1) responding to the economic conditions of Indonesia. (2) Development of technology, (3) Incorporation of Natural resources, (4) Community / user involvement, (5) Available Products and services and (6) Avaiability of Financial Resources owned or initiated by the BPPT in the Renewable Energy field. Our research found that other factors that need to be considered and even to be prioritized include (1) Policy, (2) Socio-cultural conditions, (3) Suppliers, (4) Company business partners, (5) Product development and marketing program preparation, (6) Production and operation capabilities. Keywords: Internal Resources, External Environment, Market Needs, Renewable Energy JEL Classifications: M21, Q42, Q48, Q55, Q56 DOI: https://doi.org/10.32479/ijeep.7951